Triple Social Construction of Food and Eating - Junkai Jin (Дискурс)
Introduction. Sociology of food and eating studies social practices of diet. It is necessary to include these issues in the framework of sociology of food and eating, such as how people construct food as a social object and organize social practices of diet; and how diet as a social process affects human behavior. This paper aims to show the social nature of diet and reveal the process of knowledgization and institutionalization of food and eating.Methodology. This article analyzes the social construction of food and eating, focusing mainly on three directions - sociology of things, sociology of knowledge and sociology of food and eating.Results and discussion. Social construction of food and eating is divided into three dimensions: nominal, measuring and institutional construction of food and eating. Each dimension of construction is determined by the social and structural environment.Conclusion. In the modern system of food and eating, the nominative, measuring, and institutional type of construction are in a complex and confusing state. Because of the temporal sequence of history, the knowledge system constructed by the predecessors has become "knowledge at hand ". Subsequent generations are gradually unable to recognize the complexity of multilevel social constructs of reality